READING ACHEBE’S THINGS FALL APART FROM CÉSAIRE’S PERSPECTIVE ON ANTICOLONIALISM - Tuaderu, Yohanes (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2024)
This research aims to obtain a deep notion of what stands beyond one of Achebe’s prominent African trilogies – Things Fall Apart – from the concept of anticolonialism promoted by Aimé Césaire. It examines two main subject matters i.e.; the reason why African people struggle so hard to oppose the oppression of the colonizers and what efforts they develop to react to the bad treatment. The harassment of human values - what Césaire called